PENGARUH KUALITAS AUDIT, DEBT DEFAULT DAN KONDISI KEUANGAN PERUSAHAAN TERHADAP PENERIMAAN OPINI GOING CONCERN - Alex Murtin; Choirul Anam (Journal of Accounting and Investment, 2008)
This research have a purpose to test the effect of audit quality, debt default and company financial condition to going concern opinion acceptance. The sample which used in this research is manufacture company which registered in Indonesia Stock Exchange between 2000-2007. The sample was taken with purposive sampling method and the resault 29 companies were match and fulfill the sample criteria. Hypothesis testing was done with regresion test tool from SPSS aplication program. The research result show that audit quality have positif effect and significant to the possibility of going concern opinion acceptance, debt default have positif effect and significant to the possibility of going concern opinion acceptance and company financial condition have negative  effect and significant to the possibility of going concern opinion acceptance.